Effect of Experiential Marketing on Word of Mouth with Satisfaction as Intervening Variable (Study at Go-Jek Customer in Mataram) (Global Journal of Management and Business Research, 2019)
This research is examining the effect of experiential marketing and word of mouth with satisfaction as an intervening variable on GO-JEK customers in Mataram. The type of research conducted is an associative casualty. The sample design uses non-probability sampling and the accidental sampling technique is used to determine to sample with an unknown population. The sample taken was GO-JEK customers in Mataram, which amounted to 100 samples. Data analysis uses path analysis with the smart PLS program. The Results Showed that experiential marketing had a positive and not a significant effect on word of mouth, experiential marketing had a positive and significant effect on satisfaction, and satisfaction had a positive and not a significant effect on word of mouth GO-JEK customers in Mataram. Then word of mouth is influenced by experiential marketing with satisfaction mediation. In general Go-JEK still needs to introduce its products to the community in Mataram City.
Keywords: experiential marketing; satisfaction; word of mouth